Clinical trials informed framework for real world clinical implementation and deployment of artificial intelligence applications - You, Jacqueline G.; Hernandez-Boussard, Tina; Pfeffer, Michael A.; Landman, Adam; Mishuris, Rebecca G. (NPJ digital medicine, 2025)
With rapidly evolving artificial intelligence solutions, healthcare organizations need an implementation roadmap. A “clinical trials” informed approach can promote safe and impactful implementation of artificial intelligence. This framework includes four phases: (1) Safety; (2) Efficacy; (3) Effectiveness and comparison to an existing standard; and (4) Monitoring. Combined with inter-institutional collaboration and national funding support, this approach will advance safe, usable, effective, and equitable deployments of artificial intelligence in healthcare.